Food Insecurity Is Associated With Cardiovascular and All‐Cause Mortality Among Adults in the United States - Sun, Yangbo; Liu, Buyun; Rong, Shuang; Du, Yang; Xu, Guifeng; Snetselaar, Linda G.; Wallace, Robert B.; Bao, Wei (Journal of the American Heart Association, 2020)
Background Food insecurity is a global leading public health challenge that affects not only developing countries but also developed countries, including the United States. About 50 million Americans are food insecure. In this study we examined the associations of the adult food insecurity with all-cause and cardiovascular disease mortality in a nationally representative sample of US adults. Methods and Results We included 27 188 US adults (age ≥40 years of age) who participated in the US National Health and Nutrition Examination Survey from 1999 to 2014. Food insecurity status was assessed using the Food Security Survey Module developed by the US Department of Agriculture. Mortality from all causes and cardovascular disease was ascertained through data linkage to the National Death Index through December 31, 2015. We used multivariable Cox proportional hazards regression with sampling weights to estimate hazard ratios (HRs) and 95% CIs of all-cause and cardiovascular disease mortality, according to food security status. During 205 389 person-years of the period, 5039 deaths occurred, including 1084 cardiovascular disease deaths. After adjustment for age, sex, race/ethnicity, education, income, and dietary and lifestyle factors, participants with very low food security had higher risk of all-cause and cardiovascular disease mortality, with multivariable-adjusted HRs of 1.32 (95% CI, 1.07-1.62), and 1.53 (95% CI, 1.04-2.26), respectively, compared with those with high food security. Conclusions Food insecurity is significantly associated with increased risk of excess death from cardiovascular disease and all causes in US adults.